Development of a hybrid tablet-integrated superporous hydrogel for gastro-retentive delivery of famotidine - Nilima Thombre; Kavita Chandramore; Anjali Tajanpure; Adel Al Fatease; Umme Hani; Ali H. Alamri; Mohammed Ghazwani; Roshan Jadhav; Meeta Ramaiya; Diya Anumone; Vedant Agrawal; Sharuk L. Khan; et al. (PLoS ONE, 2026)
A gastro-retentive drug delivery system based on a tablet-integrated superporous hydrogel (SPH) was developed using Famotidine as a model drug for ulcer treatment. The objective of this study was to enhance gastric retention and sustained drug release, thereby improving the bioavailability of Famotidine, a BCS Class III drug with limited permeability and incomplete absorption. The SPH system was designed to retain the formulation in the upper gastrointestinal tract, the primary site of drug absorption, and was prepared using a gas-blowing (foaming) technique. A 3² full factorial design was employed to optimize the formulation by varying the concentrations of Crosspovidone and Cassia tora as independent variables. The developed SPH formulations were evaluated for porosity, swelling index, void fraction, water retention capacity, morphology, drug–excipient compatibility, and in vitro and in vivo drug release behaviour. The optimized formulation (F1) exhibited a high cumulative drug release of 98.2191 ± 0.06%, a swelling ratio of 297.2 ± 0.11%, void fraction of 0.4366 ± 0.015, porosity of 0.171 ± 0.07, and water retention time of 0.9552 ± 0.07 min. FTIR analysis confirmed the compatibility between Famotidine and excipients, while DSC studies indicated that the drug remained in its stable form without alteration during formulation. In vivo radiographic studies demonstrated that the optimized SPH formulation remained buoyant and retained in the stomach for up to 12 h, providing prolonged gastric residence and sustained drug release. Overall, the tablet-integrated SPH system represents an effective gastro-retentive approach for enhancing the therapeutic performance of Famotidine.